Regulation of podocyte lesions in diabetic nephropathy via miR-34a in the Notch signaling pathway. Issue 44 (November 2016) - Zhang, Xiangying; Song, Shuping; Luo, Huixin
Abstract: Background: The activation of the Notch signaling pathway has been shown to play an important role in diabetic nephropathy (DN) development. Besides, Notch-1 is a target gene in miR-34a. However, the regulation of the podocyte lesions involved in DN by miR-34a has not been identified. Methods: This study utilized miR-34a mimics and small interfering RNA transfection to construct miR-34a overexpression and lower-expression model to investigate the effect of miR-34a on the regulation of the Notch signaling pathway and podocyte lesions in DN. Western blotting and real-time quantitative polymerase chain reaction were applied for the quantitative testing of mRNA and protein expression. Apoptosis of podocyte was detected by TUNEL staining. Results: In high-glucose (HG) conditions, miR-34a overexpression inhibited the expression of Notch 1, Jagged 1, NICD, Hes 1, and Hey 1 proteins. Further, cleaved caspase-3, Bax, and phosphorylation of p53 (p-p53) were reduced significantly. Therefore, miR-34a overexpression inhibited the Notch signaling pathway and podocyte lesions induced by HG. β-arrestin was slightly reduced in HG conditions. Meanwhile, miR-34a overexpression could remit the inhibition. Conclusion: Results from this study provide evidence that miR-34a may offer a new approach for the treatment of diabetes.